Everyone is lying to you : a novel - Piazza, Jo (Dutton, 2025)
"The #tradwife murder mystery we've all been waiting for. From the bestselling author of The Sicilian Inheritance and the creator of the Under the Influence podcast comes an explosive thriller about two estranged friends, a grisly murder, a sudden disappearance, and the truly shocking revelation that everyone is lying to you about something ... Lizzie and Bex were best friends in college. After graduation, Bex vanished, leaving Lizzie confused and devastated. Fifteen years later, Bex is now Rebecca Sommers, a "traditional" Instagram influencer with millions of followers who salivate over her perfect life on her ranch with her five children and handsome husband, Gray. Lizzie is a struggling magazine writer, watching reels while her young children demand her attention. One night out of the blue, Bex calls Lizzie with a career-making proposition--an exclusive interview with her about her multimillion-dollar business venture and an invitation to MomBomb, the high-profile influencing conference. At the conference, Bex goes missing and Gray is found brutally murdered on their ranch. Lizzie finds herself plunged into the dark side of the cutthroat world of social media that includes jealousy, sordid affairs, swingers, and backstabbing. She must learn who her old friend has become and who she has double-crossed to try to find her, clear her name, and maybe even save her life. Piazza's master storytelling and razor-sharp insight into the world of social media brings us a pulpy, juicy, and cleverly plotted read that will have you guessing all the way through and leave you gasping for more"--